1981
DOI: 10.1111/j.1600-051x.1981.tb00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of root surface caries in patients treated for advanced periodontal disease

Abstract: The present investigation was undertaken (1) to analyze the prevalence of root surface caries prior to and after periodontal treatment and (2) to determine the feasibility of using simple clinical criteria for predicting a patient's risk of developing root surface caries following periodontal therapy. Thirty-one patients were given advanced periodontal treatment including periodontal surgery. At baseline they were examined for oral hygiene status, root surface caries experience and number of lactobacilli per m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
61
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 17 publications
5
61
1
Order By: Relevance
“…It must be pointed out that the philosophy behind the Cariogram is already in line with these proposals. The idea of using several risk factors together is of course not new [Keyes, 1962;Rundegren and Ericson, 1978;Klock and Krasse, 1979;Ravald and Hamp, 1981;Nyman et al, 1984;Krasse, 1985;Kumagai et al, 1996]. However, the unique property of the Cariogram is that each factor, in each constellation, is 'weighted' for its cumulative input, not just added.…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that the philosophy behind the Cariogram is already in line with these proposals. The idea of using several risk factors together is of course not new [Keyes, 1962;Rundegren and Ericson, 1978;Klock and Krasse, 1979;Ravald and Hamp, 1981;Nyman et al, 1984;Krasse, 1985;Kumagai et al, 1996]. However, the unique property of the Cariogram is that each factor, in each constellation, is 'weighted' for its cumulative input, not just added.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of root caries has been found to be high in patients with untreated or treated periodontal disease [Hix and O'Leary, 1976;Ravald and Hamp, 1981;Keltjens et al" 1988], We recently reported that approximately 50% of patients referred for periodontal treatment showed one or more clinically active root caries lesions [Ravald and Birkhed, 1991], Longitudinal studies of root caries have been carried out in different populations : Ripa et al, 1987Hand et al, 1988]. In periodontally treated patients, only a few incidence studies on root car ies have been reported [Ravald and Hamp, 1981;Ravald et al.…”
mentioning
confidence: 99%
“…According to epidemiologic studies, root caries is prevalent among patients with treated and untreated periodontal disease. 22,23 Therefore, professional fluoride application is recommended to prevent root caries. Topical fluoride agents such as stannous fluoride (SnF2), NaF, and APF are used in the professional fluoride application procedure.…”
Section: Discussionmentioning
confidence: 99%